Influence of seasonality on the toxicity and metals bioavailability after the resuspension of sediments from a tropical estuary - Monte, Christiane do Nascimento; Paula de Castro Rodrigues, Ana; Galvão de Campos, Bruno [UNESP]; Moreira, Lucas Buruaem [UNESP]; Grebbe, Beatriz; de Figueiredo Eufrasio Pauly, Guacira [UNESP]; Feitosa Cruz, Ana Carolina [UNESP]; Dias da Silva, Lílian Irene; Cordeiro, Renato Campello; Moledo de Souza Abessa, Denis [UNESP]; Machado, Wilson (Elsevier, 2025)
The resuspension of polluted sediments often transfers contaminants to the water column, but the potential alterations in deposited bottom sediments remain overlooked. Guanabara Bay (GB) is a tropical estuary highly polluted by multiple sources and contaminants. This study aimed to assess possible changes of toxicity and metal pollutant retention capacity of GB sediments after resuspension, at 1h and 24h after resuspension. Sediments were collected from the Niterói Harbor (NH), Meriti River (MR), Iguaçu River (IR), Rio de Janeiro Harbor (RJH), and Guapimirim Protection Area (Guapi) in winter and summer. Whole sediment toxicity on the fecundity of Nitokra sp. was lower in the Guapi, while IR and RJH were the most toxic. Effects on the sediment-water interface were assessed by embryo-larval development of Echinometra lucunter, with higher toxicity occurring in samples from MR and RJH after resuspension, showing that resuspension increases toxicity. Resuspension increased toxicity in the sediment and water, demonstrating the paramount importance of performing ecotoxicological characterization in different periods. Furthermore, proper management of dredged materials will benefit from predictions of toxicity changes related to seasonal variability.
Keywords: Contaminants; dredging; Echinometra lucunter; Guanabara bay; Nitokra sp.; Toxicity